2011
DOI: 10.1111/j.1445-5994.2009.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Tachycardia in adults with cystic fibrosis is associated with normal autonomic function

Abstract: CF patients have normal autonomic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
1
20
2
Order By: Relevance
“…No differences were observed using controlled breathing. In contrast to the findings of Szollosi et al 3 , in the present study, children with CF demonstrated significantly higher LF values at rest compared to healthy individuals. This higher sympathetic drive can also be identified by the higher LF/HF ratio in CFG at baseline.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…No differences were observed using controlled breathing. In contrast to the findings of Szollosi et al 3 , in the present study, children with CF demonstrated significantly higher LF values at rest compared to healthy individuals. This higher sympathetic drive can also be identified by the higher LF/HF ratio in CFG at baseline.…”
Section: Discussioncontrasting
confidence: 99%
“…The plausible explanation of these results may be due to alterations of respiratory pattern 19 , higher levels of catecholamine 20 or higher work of breathing 21 ; however, these mechanisms remain speculative at this time. Szollosi et al 3 also found a negative correlation between FEV 1 % and HF (ms 2 ) during spontaneous (r: -0.54) and controlled (r: -0.57) breathing and a positive correlation between FEV 1 % and LF/HF ratio (r: 0.69) demonstrating a higher parasympathetic activation in patients presenting more obstruction to airflow. In the present study, we did not find correlations between HRV parameters and FEV 1 %; however, the mean FEV 1 % was slightly higher in our population compared to Szollosi et al 3 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…[91][92][93] Alterations in smooth muscle contractile responses to cholinergic agonists have also been described, 45,94 as has abnormal heart rate variability. 79,80 Altered autonomic function could contribute to manifestations of CF, including cough, GI motility, and mucus secretion, topics explored in greater detail further on.…”
Section: Autonomic Functionmentioning
confidence: 99%